222k views
3 votes
What’s the answer to the top question and steps how to solve?

What’s the answer to the top question and steps how to solve?-example-1
User Yorro
by
5.5k points

1 Answer

4 votes

Answer:

-3.69

Explanation:

Exponential equations can be solved by taking Ln (natural logarithm) of both sides. The rule we need to know is:


Ln(a^b)=bLn(a)

Now lets work out this problem:


16^(2x+3)=13^(x-1)\\Ln(16^(2x+3))=Ln(13^(x-1))\\(2x+3)Ln(16)=(x-1)Ln(13)

Using calculator, we take the values of Ln 16 and Ln 13 as:

Ln 16 = 2.7726

Ln 13 = 2.5649

Now, we can solve for x:


(2x+3)Ln(16)=(x-1)Ln(13)\\(2x+3)2.7726=(x-1)2.5649\\5.5452x+8.3178=2.5649x-2.5649\\2.9803x=-10.8827\\x=-3.69

x is -3.69 (rounded to 2 decimal places)

User Mathias Lund
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.